Mobile-Assisted Listening Learning: The Effect of the Learn English Listening Application on Indonesian EFL Students - Nur Indah; Masruddin; Dewi Furwana (FOSTER: Journal of English Language Teaching, 2026)
Listening is often considered one of the most challenging skills for students in English as a Foreign Language (EFL) classrooms due to limited exposure to authentic spoken English and insufficient listening practice. This study aimed to investigate the effectiveness of the Learn English Listening application in improving the listening skills of tenth-grade students at SMAN 2 Palopo. A quantitative approach with a pre-experimental one-group pre-test and post-test design was employed. The participants consisted of 20 students selected through purposive sampling. Data were collected via listening tests administered before and after the treatment and analyzed using descriptive statistics and a paired-samples t-test in IBM SPSS Statistics version 30. The results showed a significant improvement in students' listening skills, with the mean score increasing from 65.90 in the pre-test to 77.10 in the post-test. The paired-samples t-test yielded a p < .001 and a large effect size (Cohen's d = 1.586), indicating that the application produced a practically and statistically meaningful improvement in listening comprehension. These findings provide empirical evidence supporting the integration of mobile listening applications as effective digital learning tools in Indonesian EFL classrooms, particularly in contexts with limited authentic exposure to English.